2014
DOI: 10.2166/wh.2014.216
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in environmental Escherichia coli – a simple screening method for simultaneous typing and resistance determination

Abstract: We describe a simple and standardised screening system (AREB) for surveillance of antibiotic resistant bacteria in the environment. The system consists of 96 well microplates containing eight sets of breakpoint amounts of 10 different antibiotics. The incubated microplates are read by a desktop scanner and the plate images are analysed by special software that automatically presents the resistance data. The AREB method is combined with a rapid typing method, the PhenePlate system, which yields information on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…Biochemical fingerprinting of sewage isolates strongly supported this hypothesis by revealing a reduced diversity of the E. coli isolated from hospital sewage samples showing extreme resistance patterns. A similar range of E. coli diversity in hospital wastewater has been shown in studies by Kwak et al and Colque Navarro et al [15,30]. Analogous to the current study, low diversity found in a hospital wastewater sample could be attributed to the presence of highly abundant biochemical phenotypes with the same resistance pattern [30].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Biochemical fingerprinting of sewage isolates strongly supported this hypothesis by revealing a reduced diversity of the E. coli isolated from hospital sewage samples showing extreme resistance patterns. A similar range of E. coli diversity in hospital wastewater has been shown in studies by Kwak et al and Colque Navarro et al [15,30]. Analogous to the current study, low diversity found in a hospital wastewater sample could be attributed to the presence of highly abundant biochemical phenotypes with the same resistance pattern [30].…”
Section: Discussionsupporting
confidence: 89%
“…A similar range of E. coli diversity in hospital wastewater has been shown in studies by Kwak et al and Colque Navarro et al [15,30]. Analogous to the current study, low diversity found in a hospital wastewater sample could be attributed to the presence of highly abundant biochemical phenotypes with the same resistance pattern [30]. Limited diversity due to clonality emphasises the necessity for repeated sampling of sewage in order to obtain representative data, especially when hospital sewage is collected.…”
Section: Discussionsupporting
confidence: 78%
“…Up to 80 E. coli-like colonies were collected from each daily sample and subjected to PhenePlate (PhP) typing (PhPlate AB) (5, 35). The PhP system quantifies fermentation patterns for each isolate by assigning numerical values to each carbohydrate source (in 96-plate wells) as a discrete value on a scale from completely negative (25) to completely positive (0), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The colonies were simultaneously analyzed for resistance to nine antibiotics with the AREB microplates (5, 35). In total, 3,123 isolates of E.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation